Avaliação e tratamento da dor nas unidades de tratamento intensivo neonatais de Porto Alegre - Carniel, Elenice Lorenzi (2013)
Introduction: pain is a fairly recent topic in the field of neonatology, because until recently it was believed that the newborn was not able to feel pain. With the research progress we could not only to know that neonates feel pain, but also the important consequences arising from that. The aim of this study was to investigate how pain is assessed and treated in neonatal intensive care units in the city of Porto Alegre (RS). Methods: it is a descriptive study, done in the neonatal intensive care units of Porto Alegre (RS), from September/2012 to December/2012. The study was conducted in two phases: in the first, a structured interview was answered by the nurse coordinator of the neonatal intensive care unit to know if the neonatal pain is evaluated/treated and, if so, how the pain is managed; in a second moment observations were performed in loco to evaluate pain management to complement the data obtained through the interview. The observed procedures were venipuncture, gastric tube insertion, endotracheal tube aspiration, oral and nasal aspiration, heel stick and administration of medication subcutaneous/intramuscular. Results: were included in the study 9 of 10 neonatal intensive care units situated in the city of Porto Alegre (RS). Regarding the assessment of pain, 7 of 9 hospitals included in the study have established pain as the 5th vital sign, but only three have written protocol for evaluation of pain. The pain scale used by majority was the NIPS and the professionals who routinely perform pain assessment are the technical of nursing and/or nurse. Regarding pain management, of 269 procedures observed, only 31% was done with some form of analgesia. Conclusion: pain is undertreated during the procedures routinely performed by nursing staff of neonatal intensive care units of Porto Alegre.